Dynamics of photoinduced instability in ferroelectric photorefractive crystals caused by space recharging trap waves - Morozovska, A.N.; Obukhovsky, V.V.; Lemeshko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
In the paper we theoretically consider the dynamics of the inner field generated by recharging trap waves propagation and spatial-temporal features of the photoinduced light scattering caused by these phenomena in the ferroelectric photorefractive crystals with two donor levels under steady illumination by laser beam. The transverse instability of the interacting light beams plays an important role and both the photovoltaic current from each donor level and the diffusion mechanisms of carrier transfer are taken into account in the proposed theory. For the first time it has been shown that, under the definite relation between the photoionization velocities and anti-collinear Glass vectors of the donor levels, among all possible scenarios of transverse instabilities the boundary circle will be realized in the perfect crystal. Due to this phenomenon the periodical photoinduced light scattering appears in the system. The great attention has been paid to the generalization of the results in the form of master equation for the inner field dynamics and to the description of the optical autowaves generation in ilmenites. All the main theoretical results are in a good agreement with the available experimental data.